Map of erodibility classes of part of Taquari river basin, based on TM-Landsat images - Veneziani, Paulo; Santos, Athos Ribeiro dos; Crepani, Edison; Anjos, Célio Eustáquio dos; Okida, Rosana (Pesquisa Agropecuaria Brasileira, 1998)
This work discusses the contribution of the geologic and geomorphologic data from TM-LANDSAT images to obtain a erodobility classes map of the part of Taquari River Basin. This research is one of the approaches of Mulpan Project (evaluation of the potentiality of the data obtained from different sensor systems for Pantanal Mato-Grossense of physical environment surveying). This Mulpan Project has been performed under the scientific co-operation between INPE and Embrapa. The results are exemplified in this paper by the erodibility classes map from Pedro Gomes Sheet (1:100,000 scale). To the purpose of determining the relationships between erosion and geologic-geomorphologic data (indirectelly obtained by interpretation of TM-LANDSAT images), the following physical, chemical and mechanical properties of the lithologic types were specially analyzed: ruptibility-plasticity, water infiltration, runoff and landslide, complemented with identification of relief type and declivity. Intentionally, the soil and climatic data were not considered in this work with the objective to permit a good evaluation about the effective contribution of the geologic-geomorphologic data in this erosion study. This analysis allows to define 7 different erosion classes and 3 accumulation classes.